Mortality and morbidity of reusing dialysers. A report by the registration committee of the European Dialysis and Transplant Association. Issue 6141 (23rd September 1978) - Wing, A J; Brunner, F P; Brynger, H O; Chantler, C; Donckerwolcke, R A; Gurland, H J; Jacobs, C; Selwood, N H
Abstract : The practice of reusing dialysers in renal units in the UK was surveyed by examining the patient questionnaires returned to the EDTA registration committee for 1976 and by a special questionnaire sent to all UK renal units. Altogether 65.6% of the 1785 patients treated with non-disposable dialysers and 49.6% of the 1109 treated with disposable dialysers reused their equipment. Reuse of dialysers caused some morbidity but no mortality. Most centres where disposable dialysers were used accepted that their reuse was necessary because of financial constraints and was ethically defensible.